Aesthetic Encounters: Rethinking Autonomy, Space & Time In Today's World Of Art - Marianne Bertelsen (Copenhagen Business School (CBS), 2016)
By studying what goes on in the world of art, it is possible not only to make observations about art and the artist but also to understand how modern-day culture is being organized and negotiated. From this perspective, understanding the experiences of autonomy and contemporaneity in being an artist today, and how these relate to cultural structures, can serve to explain some of the cultural structures that organize the world of art. In this thesis, my empirical starting point is the local context of a Danish art school and global attitudes to cultural policy-making and art education. These attitudes, in turn, carry my research process across the global world of art, involving the local context of a Chinese art school. Moving away from the somewhat simplified conflicts of autonomy and heteronomy, the global and the local, and the traditional and the contemporary, the three main themes of autonomy, time, and space serve as essential prisms through which to understand and explain the everyday experiences of contemporary art at art schools today. This thesis is positioned as a contribution to the sociology of art but also draws on, and hopes to inspire, scholarship in global art history and aesthetic philosophy. Building upon the classic groundwork in the sociology of art I shed light on how, in an ever more changing world of art, the idea of contemporary art now involves a complex group of issues which go beyond classic approaches, and I suggest the explanatory potential of focusing on individual artists, acting in and making sense of the cultural structures of the world of art. My research process has been guided by critical realism and the methodological meta-approach of engaging with complexity through reflexive research. In this sense, the title “Aesthetic Encounters” refers not only to the conceptual and empirical results and contributions of the thesis but also to the explorative research process of engaging with the complexity of cultural and artistic worlds. As the main outcome of my research, I develop and present the concepts of “antinomies of autonomy”, globally connected but locally present contemporaneity, and the “heterochronies” of specific space-times. These are the socio-cultural dynamics which the experiences of the Chinese and Danish artists and their faculties brought me to understand. I then appropriate these dynamics as a means of rethinking and explaining some of the structural features in the world of art and the cultural developments evolving around the increased globalization of and changes in the role of the artist.
hdl:10398/9287
Keywords: 650